A transcription activation system for regulated gene expression in transgenic plants - Ian Moore; Leo Gälweiler; Debora G. Grosskopf; Jeff Schell; Klaus Palme (1998)
A widely applicable promoter system is described that allows a gene of interest to be activated in specific plant tissues after a cross between defined transgenic lines. The promoter, pOp, consists of lac operators cloned upstream of a minimal promoter. No expression was detected from this promoter when placed upstream of a β-glucuronidase (GUS) reporter gene in transgenic plants. Transcription from the promoter was activated by crossing reporter plants with activator lines that expressed a chimeric transcription factor, LhG4. This factor comprised transcription-activation domain-II from Gal4 of Saccharomyces cerevisiae fused to a mutant lac -repressor that binds its operator with increased affinity. When LhG4 was expressed from the CaMV 35S promoter, the spatial and quantitative expression characteristics of the 35S promoter were exhibited by the GUS reporter. The LhG4/pOp system may be used to study toxic or deleterious gene products, to coordinate the expression of multiple gene products, to restrict transgene phenotypes to the F1 generation, and to generate hybrid seed. The LhG4 system offers spatially regulated gene expression in the tissues of whole plants growing under normal conditions without the need for external intervention. It complements inducible expression systems that offer temporal control of gene expression in tissues that can be treated with inducing chemicals.